What is news? : an exploration of news consumption in Aotearoa New Zealand comparing older and younger audiences using a uses and gratifications lens : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate of Philosophy in Communication at Massey University, Wellington, New Zealand - Anderson, Kirsty J. (Massey University, 2025)
Technological and societal developments, including digital news, use of mobile devices, and the shared connections of social media, have impacted how and why audiences consume news. This study examined news consumption in Aotearoa New Zealand using a uses and gratifications lens, with a focus on the habits of those aged under 26 years of age and those over 26 years of age. The study produced three articles based on insights from focus groups to examine what audiences use for news, what they think is news, and what they do as a result of news. The articles indicated differences in habits between the two age cohorts, particularly in the use of social media and new media forms. Together, the articles offer three findings towards the overall research question of understanding the factors affecting news consumption and the divergence in news consumption habits between older and younger audiences. Uses and gratifications theory is still relevant for understanding news choices, as needs drive media behaviours and desired gratifications. Although news values are a useful categorisation of the characteristics of news that resonate with audiences, they need to be re-examined in the current media environment. Finally, veracity is proposed as an emerging news value as audiences have more news choice, and it is a key factor determining what news audiences consume and why. This study proposes a new theoretical model for news consumption that includes uses and gratifications theory and news values framework to understand the factors involved in news consumption. This model is explored as a case study using audiences’ responses to the media coverage of the death of Queen Elizabeth II in September 2022.
Keywords: uses and gratification, news consumption, focus groups; 470107 Media studies; 350601 Consumer behaviour